The painting techniques and workshop practices of Guido Reni - Brady, Aoife Frances (Trinity College (Dublin, Ireland). Department of History of Art and Architecture, 2017)
The intention of this thesis is to produce an account of the workshop practices of the seventeenth-century Bolognese painter, Guido Reni. Reni was a painter of great eminence in seicento Italy; a contemporary and competitor of the now more famous Caravaggio and the leading painter of the century in his hometown of Bologna. He ran a notably large workshop in the Via della Pescherie, Bologna, where his output in the first half of the seventeenth century was evidently high. In the creation of an account of Reni’s techniques and workshop, this thesis combines information from a number of sources, including seventeenth-century texts, scientific reports made by conservation departments, visual analysis of paintings, and modern scholarship. By consulting, analysing, criticising and combining these sources, certain conclusions have been drawn regarding Reni’s working methods.
Keywords: History of Art and Architecture, Ph.D.; Ph.D. Trinity College Dublin 2017